Mass Production of Dendrocalamus membranaceus Planting Stock through Culm Cuttings at Seedling Stage - Nath, S.; Das, P. K. (Indian Forester, 1995)
The vegetative propagation of Dendrocalamus membranaceus through seedling proliferation and juvenile culm cuttings at seedling stage have been studied with a view to obtain plantable saplings in massive numbers. It was observed that mother stock seedlings can be multiplied more than nineteen times without addition of fertilizer within one year. Rooting and sprouting from juvenile culm cuttings were inducted by growth promoting substance though differentially. Successful sprouting and rooting of culm segments collected from D. membranaceus seedlings had further augmented the availability of planting stock.